2019
DOI: 10.3390/f10030269
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Copper and Silver Nanoparticles on Container-Grown Scots Pine (Pinus sylvestris L.) and Pedunculate Oak (Quercus robur L.) Seedlings

Abstract: Metal nanoparticles (NPs) are finding ever-wider applications in plant production (agricultural and forestry-related) as fertilisers, pesticides and growth stimulators. This makes it essential to examine their impact on a variety of plants, including trees. In the study detailed here, we investigated the effects of nanoparticles of silver and copper (i.e., AgNPs and CuNPs) on growth, and chlorophyll fluorescence, in the seedlings of Scots pine and pedunculate oak. We also compared the ultrastructure of needles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…These results are consistent with the results of [64] in Vicia faba seedlings after seed priming by 10 ppm of AgNPs. Increasing starch grains in leaf cells may be the result of increasing photosynthetic machinery and can stimulate the accumulation of starch as a defense response against AgNPs stress [21]. However, number, shape, and size of chloroplasts were changed and the presence of spaces between thylakoids in chloroplasts was recorded at high concentrations indicating the toxic effects of AgNPs on leaf cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the results of [64] in Vicia faba seedlings after seed priming by 10 ppm of AgNPs. Increasing starch grains in leaf cells may be the result of increasing photosynthetic machinery and can stimulate the accumulation of starch as a defense response against AgNPs stress [21]. However, number, shape, and size of chloroplasts were changed and the presence of spaces between thylakoids in chloroplasts was recorded at high concentrations indicating the toxic effects of AgNPs on leaf cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that AgNPs cause ultrastructural malformation in the cells of different plants such as rice [15], barley [16], Brassica [17], tobacco [18][19][20], and Scots pine and oak [21]. Also, [22] reported obvious changes in the anatomy of the lettuce leaves in response to the Ag NPs compared to the control.…”
Section: Introductionmentioning
confidence: 99%
“…From this perspective, more aquatic [ 19 , 20 , 21 ] and wetland species [ 22 , 23 , 24 ] have been studied than terrestrial varieties. Concerning terrestrial ecosystems, to the best of our knowledge, Pinus sylvestris L. and Quercus robur L. are the only non-food terrestrial plant species to have been investigated for the exposure to ENMs [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…More aquatic and wetland species have been studied than terrestrial ones [ 32 , 33 , 34 ]. Regarding terrestrial ecosystems, as far as we know, Pinus sylvestris L. and Quercus robur L. are the only no-food terrestrial plant species investigated for the exposure to respectively nano-Ag and n CeO 2 [ 35 ].…”
Section: Introductionmentioning
confidence: 99%